The organization man. - Whyte, William Hollingsworth (Garden City Doubleday, 1957)
Regarded as one of the most important sociological and business commentaries of modern times, The Organization Man developed the first thorough description of the impact of mass organization on American society. During the height of the Eisenhower administration, corporations appeared to provide a blissful answer to postwar life with the marketing of new technologies?television, affordable cars, space travel, fast food?and lifestyles, such as carefully planned suburban communities centered around the nuclear family. William H. Whyte found this phenomenon alarming.
Keywords: Organizational commitment